2009
DOI: 10.1093/aje/kwp308
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Risk of Tuberculosis Incidence, Mortality, and Recurrence in South Korean Men and Women

Abstract: The authors explored the association of cigarette smoking with tuberculosis incidence, recurrence, and mortality. A 14-year prospective cohort study (1992-2006) was carried out in 1,294,504 South Koreans. Participants were grouped by smoking history, and the authors assessed tuberculosis incidence, mortality, and recurrence risk for each group. Unadjusted and adjusted Cox proportional hazards models were used to investigate the association between smoking history and the 3 outcomes of interest, adjusting for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
81
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 24 publications
(29 reference statements)
9
81
1
8
Order By: Relevance
“…Determinants significantly associated with tuberculosis were ever smoking and having a family history of tuberculosis, which was not a surprising finding. There have been numerous published studies reporting that smoking is associated with tuberculosis [4][5][6][22][23][24][25][26][27] and that family contacts are at high risk of tuberculosis [28][29][30][31][32]. The question is why usage of solid fuel for cooking was not significantly associated with tuberculosis in the study population, even among females.…”
Section: Discussionmentioning
confidence: 99%
“…Determinants significantly associated with tuberculosis were ever smoking and having a family history of tuberculosis, which was not a surprising finding. There have been numerous published studies reporting that smoking is associated with tuberculosis [4][5][6][22][23][24][25][26][27] and that family contacts are at high risk of tuberculosis [28][29][30][31][32]. The question is why usage of solid fuel for cooking was not significantly associated with tuberculosis in the study population, even among females.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence from a number of countries in both the developed and developing worlds attests not only to the predisposing effect of smoking for the development of pulmonary TB [105][106][107][108][109][110][111][112], but also for more severe disease progression [113], decreased efficacy of antimicrobial chemotherapy [114], prolonged infectivity [115][116][117], recurrence of disease [118], poor outcomes of multidrug-resistant TB [119] and possibly impaired post-treatment lung function [120].…”
Section: Tuberculosismentioning
confidence: 99%
“…Comorbidities, particularly DM and smoking, both of which have been associated with an increased risk of TB and poorer outcomes, [4][5][6][7] were common in our study but were not significantly associated with poor treatment outcomes. A recent systematic review reported that DM was associated with a significantly increased risk of treatment failure, death and relapse.…”
Section: Discussionmentioning
confidence: 46%